Family, Bullying and Cyberbullying - Olivas, Raul Navarro (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Despite the significant decrease in bullying that has been reported in many countries during the last two decades, bullying continues to be a significant problem among young people. Given the increase of internet use among youth, researchers have started to pay attention to cyberspace, understanding that it may be a fertile ground for bullying behaviors, specifically, what is known as cyberbullying. "Family, Bullying and Cyberbullying" examines the association of several family variables with bullying in offline and online environments during childhood and adolescence. Contributors from the Americas, Canada, Asia, and Europe offer cutting-edge research on family dynamics, bystander behaviors, parents' and educators' perceptions, and bullying and cyberbullying prevention and intervention strategies of bullying for school and home. This book also provides an analysis of the current research on the influence of family in the electronic bullying. Research topics included in the book: 1) Parental education and bullying and cyberbullying; 2) Parental monitoring and cyberbullying; 3) Parental communication and feelings of affiliation; 4) Student and educator perspective on cyberbullying; 5) Parents' responses to bullying; 6) Parental mediation and bystander behaviors; 7) Development of scales to measure cyberbullying and high internet risks. "Family, Bullying and Cyberbullying" is an essential resource for researchers, graduate students, families, and practitioners in social education, social work, teacher education, and psychology.